Pesticide mixtures detected in crop and non-target wild plant pollen and nectar - Stout, Jane (My University, 2023)
Cultivation of mass flowering entomophilous crops benefits from the presence of managed and wild pollinators, who visit flowers to forage on pollen and nectar. However, management of these crops typically includes application of pesticides, the presence of which may pose a hazard for pollinators foraging in an agricultural environment. To determine the levels of potential exposure to pesticides, their presence and concentration in pollen and nectar need assessing, both within and beyond the target crop plants. We selected ten pesticide compounds and one metabolite and analysed their occurrence in a crop (Brassica napus) and a wild plant (Rubus fruticosus agg.), which was flowering in field edges. Nectar and pollen from both plants were collected from five spring and five winter sown B. napus fields in Ireland, and were tested for pesticide residues, using QuEChERS and Liquid Chromatography tandem mass spectrometry (LC-MS/MS). Pesticide residues were detected in plant pollen and nectar of both plants. Most detections were from fields with no recorded application of the respective compounds in that year, but higher concentrations were observed in recently treated fields. Overall, more residues were detected in B. napus pollen and nectar than in the wild plant, and B. napus pollen had the highest mean concentration of residues. All matrices were contaminated with at least three compounds, and the most frequently detected compounds were fungicides. The most common compound mixture was comprised of the fungicides azoxystrobin, boscalid, and the neonicotinoid insecticide clothianidin, which was not recently applied on the fields. Our results indicate that persistent compounds like the neonicotinoids, should be continuously monitored for their presence and fate in the field environment. The toxicological evaluation of the compound mixtures identified in the present study should be performed, to determine their impacts on foraging insects that may be exposed to them.
PUBLISHED
Keywords: Herbicides; Fungicides; Insecticides; Neonicotinoids; Bees; Environmental contamination; Smart & Sustainable Planet; PESTICIDES; Pesticides, Fungicides, Herbicides; Pollinators; nectar chemistry